Disgust and OC symptoms: The Mediating Role of Harm Avoidance and Incompleteness - Ragnheiður Ragnarsdóttir 1991-; Sóley Siggeirsdóttir 1992- (2016)
An experimental study was conducted to investigate the relationship between disgust and contamination fear. The main purpose was to examine the mediating role of the two motivation dimensions of harm avoidance and incompleteness in this relationship. The final sample consisted of 84 students at the University of Iceland. Data was collected using self-report questionnaires and a behavioral avoidance task (BAT) designed to induce disgust. Results revealed that those who experienced more disgust showed less approach behavior on the BAT. Also, disgust predicted contamination fear over and above what could be accounted for by anxiety. Finally, mediational analysis using self-report questionnaires revealed that incompleteness, but not harm avoidance, was a mediating factor in the relationship between disgust and contamination fear. This suggests that it might be sensory sensitivity, rather than overestimation of threat, that explains why disgust leads to contamination related OC symptoms. However, mediational analysis using data from the BAT did not replicate these results, where neither incompleteness nor harm avoidance emerged as independent mediators.